DEVELOPMENT OF ANALYTICAL STRUCTURAL MODEL FOR COMPOSITE GRILLAGE - Dwitya Harits Waskito; Adam Sobey (Badan Riset dan Inovasi Nasional, 2020)
With the high demand and market growth for composite boats, there is a competition to design a high-quality ship which leads to thinner boat’s hull structure. To meet this objective, a highly accurate and computationally fast calculation for composite structure is needed. In ship's structure the most used configuration of the stiffeners is by using grillage. However, most of the theory of the grillage is designated for steel structure. There is a gap between steel and composites for grillage theory which will be modified especially for the deflection. There are two general methods that used in this analysis, Navier Grillage theory as the analytical method and Finite Element Analysis as the benchmark tools. To develop analytical method of composite grillages, the current method were investigated by comparing the analytical results and FEA. Two composites with high difference in Young Modulus were analyzed and the results shows that there are significant difference of results with two previous method. The deflection results of two method were analyzed with every composite elastic properties of E-Glass. Empirical equation were developed from the relation between deflection graph of two methods and composite to increase the accuracy of Navier Grillage theory for E-Glass composites grillage.